The Entrepreneurial Lens Toward The 2030 Vision in Saudi Arabia: Jeddahâ€™s Contributions to Regional Growth - Bateh, D (European Scientific Journal, ESJ, 2020)
The evolution of globalization, as many may refer to as â€œWesternizationâ€ can be measured differently from one part of the world to the next. The global mindset, which often includes a rise in entrepreneurship is one of the key markers toward growth within a nation. Countries that have much potential economically, such as Saudi Arabia, have fallen behind in economic development over the years in the area of entrepreneurship primarily due to the lack of early entrepreneurial education, policies, and culture. More recently, however, the countryâ€™s 2030 vision has been the impetus for entrepreneurs to gain support through funding, policy changes, and support through the expansion of the countryâ€™s entrepreneurial ecosystem. Jeddah, the largest port city in the Mecca (Hejaz) Region of Saudi Arabia, has taken the lead within the ecosystem, not only contributing to the growth of the country, but also to the regional economic development of the MENA region. The purpose of this research is to examine the policies, key players, and industries that lie within local entrepreneurship in Jeddah and its impact on regional economic development.